Lycopene mitigates arsenic-induced nephrotoxicity with activation of the Nrf2 pathway in mice. (3rd April 2022) - Ramadan, Shimaa S.; Almeer, Rafa; Albasher, Gadah; Abdel Moneim, Ahmed E.
Abstract: This study was designed to investigate the potential protective effect of lycopene (Lyc) against arsenic-induced nephrotoxicity. Sodium arsenite orally administered to mice for 14 days, inducing severe nephrotoxicity, in the form of hyponatremia, hyperkalemia, and elevation in the markers of kidney damage. Induction of severe inflammation, apoptosis, and oxidants/antioxidants imbalance was observed in kidney tissues. DNA damage in the form of 8-hydroxy-2′deoxyguanosine was found. However, pretreatment with Lyc prevented these consequences of arsenic poisoning in the kidneys. We suggest that Lyc exerts its nephroprotective effect via the Nrf2/HO-1 pathway, making it a promising prophylactic agent against arsenic toxicity.